2019
DOI: 10.1002/pat.4655
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel polyurethane/polypyrrole‐p‐toluenesulfonate (PU/PPy‐pTS) electroactive nanofibrous bending actuator

Abstract: Electroactive actuators based on conductive polymers currently have attracted a great deal of attention. In this study, a nanofibrous structure of polypyrrole (PPy) was used to fabricate an electroactive bending actuator. For this purpose, polyurethane/PPy (PU/PPy) nanofibrous bending actuator was fabricated through the combined use of electrospinning and in-situ chemical polymerization. The response surface methodology (RSM) was considered to find the optimal electrospinning conditions for producing PU nanofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 68 publications
(89 reference statements)
1
23
0
Order By: Relevance
“…They found that the increase of feeding rate, from 20 to 75 mL/min, had a great effect on the fibers' diameter. Ebadi et al 18…”
Section: Introductionmentioning
confidence: 99%
“…They found that the increase of feeding rate, from 20 to 75 mL/min, had a great effect on the fibers' diameter. Ebadi et al 18…”
Section: Introductionmentioning
confidence: 99%
“…during an extended healing time in in-vivo. [59][60][61] The structure of AA 40,15 sample is very similar to that of porous interconnected sponge-like native bone ( Figure 6). Usually, such a porous scaffold for bone tissue engineering is produced by using various methods such as solvent casting-particle leaching process, gas foaming, freeze-drying and phase separation.…”
Section: Ftir Of Pgs Pre-polymermentioning
confidence: 77%
“…One of the most widely used methods for the production of polymeric nanofibers is electrospinning. 5 Generally, the nanofibers can be composed of one or two components (blend) and or can have more complex structures such as coaxial and triaxial core-sheath [6][7][8] and these structures are used in various fields such as sensors and electronic, [9][10][11] actuators, [12][13][14][15][16] ion absorbance, [17][18][19] air and fluid filtration, [20][21][22] wound dressing [23][24][25][26] and burn healing, 27 adhesive and nanocomposites. 28,29 The other two important areas of nanofibers applications are drug delivery and tissue engineering.…”
mentioning
confidence: 99%
“…Similarly, the same group coated PU nanofibers with a p-toluenesulfonate doped PPy layer, resulting in electrical conductivity of approximately 276 S/cm. These nanofiber mats could be used as bending actuators [44]. To prepare scaffolds for neural cell growth, Xu et al prepared poly(l-lactide acid)-PCL fibers and coated them electrochemically with chitosan and PPy, resulting in conductivities of approximately 1 S/m [45].…”
Section: Conductive Coatingsmentioning
confidence: 99%